Willingness to Vaccinate (WTV) and Willingness to Pay (WTP) for Vaccination Against Peste des Petits Ruminants (PPR) in Mali - Wane, Abdrahmane; Dione, Michel; Wieland, Barbara; Rich, Karl M.; Yena, Awa Sadio; Fall, Abdou (Frontiers in Veterinary Science, 2020)
PPR remains a major challenge to smallholder farmers in Mali. To understand the drivers of low adoption of vaccination by farmers, we analyzed the socio-economic factors influencing farmer WTV during and in the absence of vaccination campaigns. Given that the costs associated with vaccination are largely borne by farmers, we assessed factors that associated with farmer willingness to pay (WTP) more than the current price (150 XOF per dose) by considering two attributes of improvement of the vaccines empirically highlighted as potential leverage points for intervention: access of farmers to vaccines (reducing the distance to the vaccine) and availability of information about the quality of the vaccine ( introducing a vaccine viability detector) . Data were collected in Mopti and Sikasso regions from 304 producers. Overall (n=304), 89 percent of respondents vaccinated their herds during official vaccination campaigns. They are associated with receiving information on the campaign calendar more quickly if information is relayed at places of worship and if they have an awareness of the benefits of vaccination, including the protection of third parties. Only 39 percent of respondents vaccinate outside vaccination campaigns. They are positively linked to the credibility of private veterinarians and a recognition of the vital importance of vaccines but are negatively associated with ignorance of vaccination needs and concern about vaccine side-effects. Both distance-effects and quality-tracker effects are associated with farmer willingness to pay more than the current vaccine prices. Farmers practicing semi-intensive production systems are willing to pay 20 percent more than the current vaccine prices, as are users who believe in the beneficial effects of vaccination, users who consider the prices of vaccines as fair, and those who believe that some vaccines are more important than others. Factors that discourage producers from vaccinating or from paying more for vaccination would be more effectively managed with better communication on vaccine benefits through targeted information dissemination campaigns by Malian authorities. Greater price transparency throughout the vaccine production and deployment chain is critical, while timely availability of vaccine tested for viability would increase the willingness to vaccinate while improving access.